Mortalidade e injúrias em larvas de peixes associadas à passagem descendente por barragens hidrelétricas : protocolo de avaliação e estudo de caso. - Alves, Diego Corrêa (2015)
The implementation of hydropower projects is a major threat to the ichthyic diversity worldwide, especially affecting the species that make large reproductive migrations. The interruption of river connectivity causes the locking connection among habitats that are essential to the life cycle of these species. The downstream drift of ichthyoplankton can be difficult when the reservoirs act as barrier. Passed this stretch, the dam itself remains a challenge to recruitment, since the dams structures have the potential to cause injury or even death of these organisms. Although the knowledge about the passage of ichthyoplankton by hydroelectric reservoirs and dams is critical to the development of effective conservation strategies, their survival rates are largely unknown. Thus, the goal of this study was to propose an approach to evaluate in situ the association between injury or mortality of fish larvae and its passage downstream through dams and apply the sampling and analytical designs proposed to a case study on Santo Antônio dam, Madeira river, Brazilian Amazon.